Whole genomic sequencing and sex-dependent abundance estimation of Cardinium sp., a common and hyperabundant bacterial endosymbiont of the American house dust mite, Dermatophagoides farinae - Erban, Tomas; Klimov, Pavel; Molva, Vit; Hubert, Jan (Experimental & applied acarology, 2020)
The two common species of house dust mites (HDMs), Dermatophagoides farinae and D. pteronyssinus, are major sources of allergens in human dwellings worldwide. Many allergens from HDMs have been described, but their extracts vary in immunogens. Mite strains may differ in their microbiomes, which affect mite allergen expression and contents of bacterial endotoxins. Some bacteria, such as the intracellular symbiont Cardinium, can affect both the sex ratio and biochemical pathways of mites, resulting in abundance variations of mite allergens/immunogens. Here, we investigated the bacterial microbiomes of D. farinae and D. pteronyssinus males and females using barcode 16S rDNA sequencing, qPCR, and genomic data analysis. We found a single species of Cardinium associated with D. farinae strains from the USA, China and Europe. Cardinium had high abundance relative to other bacterial taxa and represented 99% of all bacterial DNA reads from female mites from the USA. Cardinium was also abundant with respect to the number of host cells-we estimated 10.4-11.8 cells of Cardinium per single female mite cell. In a European D. farinae strain, Cardinium was more prevalent in females than in males (representing 92 and 67% of all bacterial taxa in females and males, respectively). In contrast, D. pteronyssinus lacked any Cardinium species, and the microbiomes of male and female mites were similar. We produced a Cardinium genome assembly (1.48 Mb; GenBank: PRJNA555788, GCA_007559345.1) associated with D. farinae. The ascertained ubiquity and abundance of Cardinium strongly suggest that this intracellular bacterium plays an important biological role in D. farinae.
Keywords: Dermatophagoides pteronyssinus; Whole Genome Sequencing; genom bakteriální; Dermatophagoides farinae; Cardinium; Europe; Astigmata; China; Microbiome; Male; Genome, Bacterial; Evropa; Symbiosis; symbióza; Animals; sekvenování celého genomu; mikrobiota; Acaridida; Microbiota; Allergen production; zvířata; mužské pohlaví; Spojené státy americké; Bacteroidetes; ženské pohlaví; Čína; Female; United States